2004
DOI: 10.1021/jo049859f
|View full text |Cite
|
Sign up to set email alerts
|

Improved Chemical Syntheses of 1- and 5-Deazariboflavin

Abstract: The cofactor flavin adenine dinucleotide (FAD) is required for the catalytic activity of a large class of enzymes known as flavoenzymes. Because flavin cofactors participate in catalysis via a number of different mechanisms, isoalloxazine analogues are valuable for mechanistic studies. We report improved chemical syntheses for the preparation of the two key analogues, 5-deazariboflavin and 1-deazariboflavin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…However, their application in biological systems and their physicochemical characterization is still limited due to synthetic difficulties, and improvement of their generation is clearly needed. The synthetic pathways for all four flavins reported in this paper started from available substituted anilines, which were further converted into the corresponding riboanilines in one step and high yield under reductive amination conditions, similar to the proposal by Kiessling et al [20] The key step in the preparation of compounds 4-7 was the elaboration of the corresponding riboaniline derivatives into the complete isoalloxazine ring. According to our aims and commercially available sources, we chose three different synthetic pathways: a) via coupling with 6-chlorouracil; b) via condensation with alloxane, and c) building the deazauracil ring in parts.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, their application in biological systems and their physicochemical characterization is still limited due to synthetic difficulties, and improvement of their generation is clearly needed. The synthetic pathways for all four flavins reported in this paper started from available substituted anilines, which were further converted into the corresponding riboanilines in one step and high yield under reductive amination conditions, similar to the proposal by Kiessling et al [20] The key step in the preparation of compounds 4-7 was the elaboration of the corresponding riboaniline derivatives into the complete isoalloxazine ring. According to our aims and commercially available sources, we chose three different synthetic pathways: a) via coupling with 6-chlorouracil; b) via condensation with alloxane, and c) building the deazauracil ring in parts.…”
Section: Introductionmentioning
confidence: 74%
“…The introduction of the uracil component was performed by coupling 14 with 6-chlorouracil. Although several alternative conditions of this step have been published, [20][21][22][23][24][25] this coupling still remains the most chal-lenging step due to the relatively low yield and problems with the isolation of the final product 15. In particular, we found that the use of freshly prepared 6-chlorouracil under carefully maintained dry conditions significantly increases the yield of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…A tert-butyloxycarbonyl protecting group was employed as before, 1 with protection achieved at ambient temperature (using a strict stoichiometric amount of the anhydride) in 92% yield, compared to 66% reported previously. 1 Ribitylation of mono-protected intermediate 9 was also performed according to the same procedure; 1 however, it was found that the acid-labile Boc protecting group was readily cleaved during the work-up of the reaction (performed using aqueous hydrochloric acid), even with short exposure times. This was problematic as the resultant deprotected ribitylated intermediate 3 was highly soluble in the aqueous solution, which was also contaminated by other reaction by-products.…”
Section: Resultsmentioning
confidence: 99%
“…1 However, it was observed that while ribitylated diamine 3 was soluble in high-polarity solvents (and insoluble in non-polar solvents), diethyl 2-bromo-3-oxogluarate 4 was only soluble in non-polar solvents and insoluble in polar solvents. The poor miscibility of the chosen solvents appeared, not unreasonably, to play a deleterious role in the mediocre yield of this reaction stage, and which was highly reproducible; several strategies were considered to improve the mixing of the reactants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation